An Exploratory Qualitative Study on the Perceived Barriers to Accessing Ghanaian University Counselling Services (Journal of Student Affairs in Africa, 2022)
Despite research emphasis on university students’ counselling needs and service benefits, barriers to counselling service participation for students have been less explored in Ghanaian higher education. Yet literature is replete with reports on high undergraduate student attrition and a low sense of belonging, stressing the severe need for increased counselling service participation among students in higher education. This article explored the barriers to increased counselling service participation faced by Ghanaian public university students. Our research engaged 13 counselled undergraduate students, purposively selected via snowball and convenience sampling techniques. We engaged study participants in in-depth interviews and a focus group discussion to gather appropriate data and further used the interpretive phenomenological approach to find meaning in the gathered data. Students revealed their perceptions on poor counsellors’ sense of initiative, their low service awareness, and their misconceptions which seem to hinder students’ counselling service participation. Our results underscore the need for more service advertising and possibly increased counsellor initiative to promote counselling service use among higher education students in Ghana. Daily service advertising with counsellors’ reliance on text and WhatsApp messaging, still pictures and short videos on the various campuses (Amos et al., 2020) would considerably increase students’ awareness of counselling services.
Keywords: Counselling, academic achievement, higher education, student support service